Westly a spider's tale - Beus, Bryan (Shadow Mountain, 2015)
Westly is as ready as his caterpillar friends to keep their beautiful territory free of lesser creatures as they await the day they turn into delicate butterflies, but when he finally emerges from his crysalis, he discovers he is vastly different from his friends.
Keywords: Friendship -- Fiction; Prejudices -- Fiction; Spiders -- Fiction; Butterflies -- Fiction; Moths -- Fiction; Race relations -- Fiction; American fiction -- 21st century